Targeting PD-L1 for non-small-cell lung cancer. (June 2016) - Feld, Emily; Horn, Leora
Lung cancer is the leading cause of cancer-related death worldwide. For decades, cytotoxic chemotherapy has been the mainstay of treatment for the majority of patients, yet median survival remains poor and side effects from chemotherapy are not trivial. Immune checkpoint inhibitors, which exert antitumor effects by inhibiting negative T-cell regulators, are changing the landscape of treatment options for patients with non-small-cell lung cancer (NSCLC). The anti-PD-1 antibodies nivolumab and pembrolizumab are approved by the US FDA for treatment of patients with NSCLC and other tumor types. Additional agents are in clinical development. This review provides an update on the PD-1 and PD-L1 immune checkpoint inhibitors currently being evaluated in NSCLC patients.